Roles of Artificial Intelligence in Promoting Education for Sustainable Development in Lower-Middle-Income ASEAN Economies - Hara, Masatoshi (American Journal of Business Science Philosophy, 2024)
This study examines the role of artificial intelligence (AI) in promoting Education for Sustainable Development (ESD) in lower-middle-income ASEAN economies, focusing on two critical areas: the challenges to AI adoption and strategies to optimize AI alignment with sustainable development goals. The research identifies key barriers to AI integration, including technological readiness, financial constraints, policy gaps, and socio-cultural factors, through document analysis and case studies. It highlights region-specific challenges, such as inadequate digital infrastructure and limited teacher training, that hinder AI adoption in education. Additionally, the study explores how AI can be optimized to support Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education) and SDG 9 (Innovation and Infrastructure), by enhancing educational access, promoting gender equality, and enabling personalized learning. Using the Grounded Theory model, the findings suggest that AI can reduce inequalities and empower underserved communities by improving educational outcomes. However, successful AI integration requires a balanced approach that prioritizes ethical considerations and inclusivity. The study advocates for collaborative efforts between governments, educational institutions, and technology providers to establish an ecosystem that supports responsible AI deployment. By addressing these challenges and leveraging AI’s potential, stakeholders can unlock new opportunities to foster sustainable development and improve educational outcomes in ASEAN lower-middle-income economies.
Keywords: artificial intelligence; education; sustainable development; ASEAN